Cost analysis of screening according to ECCO guidelines for prevention of opportunistic infections in infliximab-treated ibd patients. (13th March 2011) - Metz, A; Elliott, T; Hull, B; Duncan, J; Sastrillo, M; Smith, M; Sanderson, J D; Irving, P M
Abstract : Introduction: We previously reported that our practice of screening for and prevention of opportunistic infections (OI's) in at risk IBD patients was not in line with ECCO recommendations.1 2 In this study, we aimed first to seek evidence of OI's in our historical cohort of infliximab (IFX)-treated patients who had not been screened according to recommendations and second, to analyse the cost-effectiveness of screening of, and prophylaxis as required for tuberculosis (TB) and hepatitis B (hep B) in IFX-treated patients. Methods: An audit of consecutive patients treated with IFX (2005–2009) was conducted and occurrence of OIs and duration of IFX were recorded. A cost-minimisation analysis was performed using clinical decision analytic modelling to assess cost outcome of screening and prevention versus not screening and prevention. Model branch probabilities were obtained from a Medline search. The cost perspective was the health sector. Hospital admissions were based on Healthcare Resource Group (HRG4) codes. Results: There were no OI's identified in 92 IBD patients treated with a median of 21 months of IFX. For 1000 hypothetical Crohn's patients in a western European population, the model predicted 15 screened patients required isoniazid prophylaxis, with 0.5 unscreened patients admitted to hospital with TB. There was an incremental cost for screening of £39.50/patient for CXR alone, or £125.60 for CXR combined with an interferon release assay. Conversely, there was a cost saving for screening in Southern Europe (£12/patient). For Hepatitis B in the Western European population, the model predicted 35.7 screened patients required lamivudine prophylaxis, whereas in the unscreened group, 2 patients reactivated with hepatitis, 3 patients with liver failure, and one required a transplant. There was a cost saving of £32/patient for screening. Conclusion: There were no significant OI's identified in this audit of IFX-treated IBD patients despite failure to screen according to ECCO guidelines. The cost analysis model demonstrates cost saving for hepatitis B screening because of the significant cost of hepatitis B reactivation. In the southern European population there is a cost benefit for TB screening due to a high rate of latent TB whereas in the western European population, there is an incremental cost for screening because of a lower risk of TB reactivation there. This cost should be balanced against the risk of death due to TB reactivation (reported in Southern but not Western Europe).3